MODEL PENANGANAN KONFLIK SOSIAL DI KECAMATAN KATOBU KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - Nasruddin Suyuti; La Ode Aris (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This article is the result of research with the title “analysis of social conflict in Muna society implemented in Katobu District Muna Regency”. Objective of this study was to determine the cause of social conflict in the Katobu District Muna Regency, and to know how to make a model of handling of social conflicts that occurred in the Katobu District, The study was planned for two years. The first year was 2015 had been implemented. The results of the first year of research showed that the cause of social conflict in Muna is the consumption of alcohol, misunderstanding between youths, planned violence, and conflict of interest. While the second year is 2016, the writer is trying to create a model format on handling social conflicts in Muna. This research method used in this study is a qualitative research method. To get the field data, the techniques used were techniques of observation, interviews, and documentation. While the source of the data used are primary data and secondary data. Primary data is data obtained directly on the object of study or directly to the public, while secondary data is data obtained from documents or previous research results. These results indicate that the handling of social conflicts in Katobu District Muna Regency is through improving the skills of youth, opening of new jobs, and increase the intensive communication between communities. While the model of conflict resolution after extensive research it is necessary to disseminate to the government about the findings of the field in accordance with the possibility of social conflict that can be occured, after that government should make policies to implement some of the findings from the field, so that social conflict can be minimized or even eliminated.